Experimental investigation on erosion resistance of iron boride coatings for steam turbines at high temperatures. (May 2015) - Cai, Liu-xi; Mao, Jing-ru; Wang, Shun-sen; Di, Juan; Feng, Zhen-ping
In this paper, high temperature erosion tests are performed on four typical anti-erosion coatings for high-parameter steam turbine blades using pneumatic accelerated erosion method to simulate the actual erosion environment in power units. With the employment of scanning electron microscope, energy-dispersive X-ray spectroscopy, glancing-angle X-ray diffraction, and Vickers indentation testing techniques, detailed microscopic analysis of samples is conducted to reveal the underlying causes affecting the anti-erosion performance of coatings. Results show that, under the solid particle erosion at high temperature, boride coatings with more compact structure and higher hardness have stronger anti-erosion ability, whose erosion rate is only 30–50% that of HVOF Cr3 C2 coatings under the same erosion condition. Boride coatings composed of duplex phase (FeB and Fe2 B) have lower anti-erosion damage capability than that of boride coatings composed of single Fe2 B phase. Under high-speed large incidence angle impingement, the surface layer of FeB cracks easily and rapidly propagates to the subsurface layer Fe2 B phase under the sustained impingement from particles, resulting in the flaking off and failure of coatings. Single Fe2 B phase boride coatings have smaller hardness gradient in the depth direction and higher fracture toughness than boride coatings composed of duplex phase, so that exhibit more stable excellent erosion resistance under different erosion parameters. Therefore, single Fe2 B phase boride coatings should be used as the preferred wear resistant coating for turbine blades solid particle erosion problem.